Natalizumab Induces Changes of Cerebrospinal Fluid Measures in Multiple Sclerosis - Ganapathy Subramanian, Ranjani; Horakova, Dana; Vaneckova, Manuela; Lorincz, Balazs; Krasensky, Jan; Kubala Havrdova, Eva; Uher, Tomas (Diagnostics (Basel, Switzerland), 2021)
BACKGROUND: There is a lack of knowledge about the evolution of cerebrospinal fluid (CSF) markers in multiple sclerosis (MS) patients undergoing natalizumab treatment. AIM: We aimed to evaluate the effect of natalizumab on basic inflammatory CSF and MRI measures. METHODS: Together, 411 patients were screened for eligibility and 93 subjects with ≥2 CSF examinations ≤6 months before and ≥12 months after natalizumab initiation were recruited. The effect of natalizumab on CSF as well as clinical and paraclinical measures was analyzed using adjusted mixed models. RESULTS: Natalizumab induced a decrease in CSF leukocytes (p < 1 × 10-15), CSF protein (p = 0.00007), the albumin quotient (p = 0.007), the IgG quotient (p = 6 × 10-15), the IgM quotient (p = 0.0002), the IgG index (p = 0.0004), the IgM index (p = 0.003) and the number of CSF-restricted oligoclonal bands (OCBs) (p = 0.0005). CSF-restricted OCBs positivity dropped from 94.6% to 86% but 26 patients (28%) had an increased number of OCBs at the follow-up. The baseline to follow-up EDSS and T2-LV were stable; a decrease in the relapse rate was consistent with a decrease in the CSF inflammatory markers and previous knowledge about the effectiveness of natalizumab. The average annualized brain volume loss during the follow-up was -0.50% (IQR = -0.96, -0.16) and was predicted by the baseline IgM index (B = -0.37; p = 0.003). CONCLUSIONS: Natalizumab is associated with a reduction of basic CSF inflammatory measures supporting its strong anti-inflammatory properties. The IgM index at the baseline predicted future brain volume loss during the course of natalizumab treatment.
Keywords: brain atrophy; oligoclonal bands; multiple sclerosis; MRI; cerebrospinal fluid; natalizumab